Hypothyroid coma and thyrotoxic crisis. - Soares, A de D; Falcão, L M; De Barros, E (Acta Médica Portuguesa, 1997)
Two clinical cases of endocrinologic emergency are presented: myxedema coma and thyrotoxic crisis. These are very severe situations with a high mortality rate. In myxedema coma it reaches 50% and in thyrotoxic crisis the range is between 25 and 30%. These entities are not the always present in mind because of their rarity. Consequently, they may well be undiagnosed. In our cases, the myxedema coma was initially diagnosed as brainstem stroke, and the hyperthyroidism was taken for concealed malignant tumor. The management of both situations is briefly commented.